The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s10909-019-02210-w
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Oscillations and Anomalous Current States in a Photoexcited Electron Gas on Liquid Helium

Abstract: The paper reviews a novel class of phenomena observed recently in the two-dimensional (2D) electron system formed on the free surface of liquid helium in the presence of a magnetic field directed normally and exposed to microwave radiation. The distinctive feature of these nonequilibrium phenomena is magnetoconductivity oscillations induced by inter-subband (out-of-plane) and intra-subband (in-plane) microwave excitations. The conductivity magneto-oscillations induced by intra-subband excitation are similar to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
3
9
0
Order By: Relevance
“…3(a) is almost independent of V and n e . It may arise from the interaction of surface electrons with gravity waves, also known as ripplons [23,27]: for radially symmetric modes, the lowest resonant frequency is f ≈ 0.609 √ gd/R, where g is the acceleration due to gravity, and d and R are respectively the height and radius of the circular liquid pool [33]. This yields 5.28 Hz, comparable with the observations.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…3(a) is almost independent of V and n e . It may arise from the interaction of surface electrons with gravity waves, also known as ripplons [23,27]: for radially symmetric modes, the lowest resonant frequency is f ≈ 0.609 √ gd/R, where g is the acceleration due to gravity, and d and R are respectively the height and radius of the circular liquid pool [33]. This yields 5.28 Hz, comparable with the observations.…”
supporting
confidence: 74%
“…In conclusion, we have confirmed that the main kHz signals are generated by inter-edge magnetoplasmons [34] modulated by interaction with surface ripplons at about 5 Hz [23,27]. Note that, in attributing the ∼ 5 Hz modulation to the effect of ripplons, we are effectively taking account of vertical motion, i.e.…”
supporting
confidence: 67%
See 3 more Smart Citations